Employer Perceptions of Online Degrees: A Literature Review - Norina L. Columbaro; Catherine H. Monaghan (Adult Education Research Conference, 2008)
This literature review explores the research about the perception of online degrees by potential employers or “gatekeepers” in comparison with those earned in a traditional format. This is important because these perceptions can affect the employment opportunities or lack thereof of students and, in turn, institutions.
Keywords: online degrees; higher education; virtual college; hiring; perceptions; academic degree programs